STANDARDIZING PHYSICAL TRAINING FOR STUDENTS IN FOOTBALL - Raximov A. A. (Bright Mind Publishing, 2025)
The article discusses the main aspects of assessing students' physical fitness in football.
Keywords: Football, student, physical training, futsal, strength and endurance exercises, increasing speed, running short and long distances, developing coordination and balance.